Proteomic analysis to identify biomarkers in the primary tumour that predict response to neoadjuvant chemotherapy in liver metastases. (26th February 2015) - Sutton, Paul; Evans, Jonathan; Jones, Robert; Malik, Hassan; Vimalachandran, Dale; Palmer, Daniel; Goldring, Chris; Kitteringham, Neil
Abstract: Background: Colorectal cancer is the fourth commonest cancer in the UK, and the second commonest cause of cancer-related death. A knowledge of the biological phenotype of colorectal liver metastases would be invaluable to inform clinical decision making; however, deriving this information from the metastatic lesions is not feasible until after resection. We aimed to use proteomic analysis to identify biomarkers in the primary tumour that predict response to neoadjuvant chemotherapy in liver metastases. Methods: Fresh tissue from both primary colorectal tumour and liver metastases from 17 patients was subjected to proteomic analysis using isobaric tagging for relative quantification. Data were analysed with Protein Pilot (Ab Sciex, Framingham, MA, USA), with stratification of patients into those showing low or high response to chemotherapy permitting the identification of potential predictive biomarkers. These markers were subsequently validated by immunohistochemistry on a tissue microarray of 63 patients. Findings: We identified 5768 discrete proteins. Five of them predicted histopathological response to fluorouracil-based chemotherapy regimens, of which the FAD binding protein NQO1 was subsequently validated by immunohistochemistry. When compared with the chemotherapeutic agent alone, knockdown of the corresponding gene with small interfering RNA decreased cell viability when co-incubated with fluorouracil (77·1% vs 46·6%, p=0·037) and irinotecan (41·7% vs 24·4%, p=0·006). Similar results were also seen after inhibition of protein activity by pretreating cells with dicoumarol. Interpretation: These results show that proteomic sequencing of matched metastatic colorectal cancer samples is feasible, with high protein coverage. The high degree of similarity between the primary and secondary proteomes suggests that primary tissue is predictive of the metastatic phenotype. NQO1 expression in the primary tumour predicts response to neoadjuvant chemotherapy in the liver metastases, and inhibition of this protein at both genetic and functional levels improves chemosensitivity. Funding: Cancer Research UK.